Electronic and optical properties of CaCl2 using Compton scattering and density functional theory. (September 2018) - Kumawat, Ashok; Sahariya, Jagrati; Kumar, Kishor; Ahuja, B.L.
Abstract: In this paper electron momentum density of CaCl2 using 241 Am Compton spectrometer is reported. The experimental Compton profile is compared with the corresponding theoretical profiles, computed using different exchange and correlation potentials within linear combination of atomic orbitals (LCAO) scheme. The hybrid WC1LYP approximation within LCAO scheme shows a better agreement with experimental CP than other reported theoretical profiles. Going beyond Compton line shapes, the energy bands, density of states using LCAO scheme and modified Becke-Johnson (mBJ) potential within full potential linearized augmented plane wave (FP-LAPW) method are also reported. The optical properties like, dielectric tensors, absorption spectra, reflectivity and refraction are also discussed using FP-LAPW method. Energy band gaps computed using LCAO-WC1LYP and FP-LAPW-mBJ methods are found to be 6.89 and 6.76 eV, respectively which are in reasonable agreement with the available experimental data. Highlights: Experimental Compton profile (CP) of CaCl2 is measured using 241 Am source. Experimental CP is compared with LCAO based profiles. Energy bands & DOS are computed using LCAO & FP-LAPW schemes. Optical properties of CaCl2 are deduced from mBJ schemes.